Comparison of Female Athlete Triad (Triad) and Relative Energy Deficiency in Sport (RED-S): a review of low energy availability, multidisciplinary awareness, screening tools and education - Warrick, A.; Faustin, M.; Waite, B. (Current Physical Medicine and Rehabilitation Reports, 2020)
Purpose of Review: This paper aims to review low energy availability (low EA), compare the Female Athlete Triad (Triad) and Relative Energy Deficiency in Sport (RED-S) screening tools and eating disorder/disordered eating questionnaires, and discuss multidisciplinary awareness, education, and treatment strategies. It provides an overview on the current state of the Triad and RED-S and assists clinicians with an overview of options for screening tools for their practice. Recent Findings: Triad Consensus Panel Screening Questions, Preparticipation Physical Exam (PPE), and Periodic Health Exam (PHE) share overlapping questions from the Triad Consensus Panel Screening Questions. The Low Energy Availability in Females Questionnaire (LEAF-Q) is used in complement with eating disorder/disordered eating questionnaires (Table 2). Summary: It is important to screen athletes for low EA during the PPE. If concerned for low EA, referral to healthcare professional and registered dietician is warranted. Education for athletes, coaches, and multidisciplinary providers is needed to increase awareness of low EA.